The Nexus of Women's Education and Social Stability: A Case Study on Conflict Mitigation in Indonesia - Siti Mubayanah Tawabie; Raharjo Raharjo (CV. Bimbingan Belajar Assyfa, 2025)
In today's era of globalization and digitalization, critical thinking skills, emotional intelligence, and social literacy are crucial competencies that students must possess to navigate complex societal dynamics. Integrative and humanistic peace education is seen as an effective, creative strategy for enhancing students' mediation and empathy skills in a multicultural environment. This research is motivated by the limited research on the substantive role of women in social stability, with most studies evaluating formal political participation without addressing the grassroots. This study evaluates the effectiveness of non-formal education in strengthening women's roles and its impact on community resilience in post-conflict areas in Indonesia, particularly on the development of cognitive and psychomotor skills in the negotiation process. The primary objective of the study is to analyze the causal relationship between women's education levels and the effectiveness of social conflict mitigation. The method used is a qualitative case study design, employing thematic analysis techniques and data collection through in-depth interviews and participant observation, supported by qualitative data analysis tools. The study's results demonstrate a significant positive impact on the conflict resolution capacity of educated women, with leadership training serving as a crucial scaffolding. However, it was found that formal higher education without integrating mediation values ​​had no significant impact on the success of mitigation efforts in the field. In conclusion, strengthening women's education based on peace values ​​has vital implications as a foundation for sustainable social stability in Indonesia.